Modelling the mechanisms of microsilica particle formation and growth - González-Fariña, R (2020)
Microsilica particles arise as a byproduct of silicon furnace operation, created inside high temperature flames due to the combustion reaction of silicon monoxide with oxygen. These nanoparticles, which grow as silicon dioxide vapour condenses on the surface of existing particles, are used in a variety of composite materials. The size and quality of the particles affect the performance of the material used for such applications, and hence control of these quantities is of importance to manufacturers.